Ambient Noise Tomography Around The Banda Arc Study Case: Before Earthquake of February 2nd, 2022 - Raharjo, Wiji; Palupi, Indriati Retno; Madona, Madona (Geological Agency, 2025)
Banda Arc is one of the vulnerable areas in Indonesia. It is trapped by the slab coming from AustralianEurasian Plate with the S ̶ N direction and the slab coming from Pacific Plate with the E ̶ W direction. Because of its location, it has a high seismicity, for example there was an earthquake that raised a big tsunami in 1852. On February 2nd, 2022, the newest earthquake with magnitude of 6.2 hit the Banda Arc. In many cases, earthquakes are damaging disasters, because their surface waves are shocking through anything they pass. Nowadays the surface wave is used to get the subsurface description and the variation of its velocity, and ambient noise tomography (ANT) is one way to solve it. By using some analyses like cross correlation and fast fourier transform (FFT) from the earthquake waveform three days before February 2nd, 2022, the depth and velocity group around the Banda Arc can be known. There is an indication that it was influenced by the ocean wave, which became wider and close to the main shock. Besides that, ANT result shows that the low velocity anomaly was distributed around the deepest area of the Banda Arc, because the energy absorbed more there, besides in the near location of hypocenter and resulting low velocity anomaly. It is shown that the low velocity anomaly can show how the geological condition is.